Small Sounds in Familiar Places: A Poetic-Visual Inquiry on the Gravity and Synchrony of Love in Pandemic Times - Levesque, Lauren Michelle (Art/Research International, 2022)
In this article, the movement between the gravity and synchrony of love in pandemic times as revealed through the creative practices of poetry and cellphone photography is addressed. Informed by literature on slow scholarship published prior to and during the COVID-19 pandemic, the author explores the ways in which listening to and caring for the small sounds of a familiar place–here a rural backyard–can act as a generative theoretical space to reconsider the meaning of love and its implications for academic work. The principal questions include: how can the practice of writing poems and taking photographs foster the intentionality of slow time? How can immersing oneself in this time provide insight into perhaps worn-out conceptualizations of what is considered precious? What implications, if any, can these insights have for understandings of love and the need for slow scholarship post-pandemic?